A Novel Power Electronic Inverter Circuit for Transformerless Photovoltaic Systems - Cao Hai-Yan (Active and Passive Electronic Components)
Capacitive leakage current is one of the most important issues for transformerless photovoltaic systems. In order to deal with the capacitive leakage current, a new power electronic inverter circuit is proposed in this paper. The inverter circuit consists of six switches and operates with constant common mode voltage. Theoretical analysis is conducted to clarify the circuit operation principle and the common mode characteristic. The performance evaluation test is carried out, and test results demonstrate that the capacitive leakage current can be significantly minimized with the proposed power electronic inverter circuit.